Single dosing comparison of the relative cardiac beta 1/beta 2 activity of inhaled fenoterol and salbutamol in normal subjects. Issue 6 (June 1993) - Newnham, D M; Wheeldon, N M; Lipworth, B J; McDevitt, D G
Abstract : BACKGROUND–The aim of the present study was to compare the dose related effects of fenoterol and salbutamol on cardiac beta 1 and beta 2 receptors using the beta 1 selective antagonist atenolol, in order to dissect out relative beta 1/beta 2 mediated responses. METHODS–Fourteen normal volunteers were randomised to receive pretreatment with either atenolol 25 mg or placebo, followed by inhaled fenoterol or salbutamol in equal doses by weight (cumulative doses of 1 mg and 4 mg). Measurements were made 30 minutes after inhaling each dose of beta 2 agonist. Values (mean and 95% CI) were expressed as a change from baseline. RESULTS–At 4 mg fenoterol produced equivalent falls in serum potassium and increases in tremor to salbutamol. The mean (95% CI) increase in heart rate (beats/min) with fenoterol at 4 mg after placebo was 47 (41-53) and after atenolol was 34 (28-40), with values for salbutamol being 46 (40-52) after placebo and 30 (24-36) after atenolol. The inotropic response (stroke distance) after atenolol at the 4 mg dose was 5.0 (3.9-6.1) cm for fenoterol and 4.7 (3.5-5.9) cm for salbutamol. There were no significant differences in heart rate or stroke distance response between the two drugs after either placebo or atenolol. Furthermore, ECG effects (Q-Tc and T wave) of fenoterol and salbutamol were comparable at both doses. CONCLUSIONS–These results show that there is no difference in the respective chronotropic or inotropic activities of fenoterol and salbutamol on cardiac beta 1 or beta 2 receptors when given at higher than conventional doses.